Nuclear ING3 Expression Is Correlated With a Good Prognosis of Breast Cancer - Wu, Xiaoyan; Chen, Chuang; Luo, Bin; Yan, Dandan; Yan, Honglin; Chen, Fangfang; Guan, Feng; Wu, Hao; Yuan, Jingping (Frontiers in Oncology, 2021)
Abstract The inhibitor of growth (ING) family was discovered as the type II tumor suppressors, which regulated the proliferation, apoptosis, differentiation, angiogenesis, metastasis, and invasion of tumor cells through multiple pathways. ING3, a new member of ING family, has been reported to be downregulated in several types of tumors. However, few studies on ING3 in breast cancer have been reported. In this study, we investigated the expression of ING3 and determined its prognostic value in breast cancer. The immunohistochemistry was performed to evaluate the expression of ING3 in tissue microarrays (TMA) including breast cancer tissues (n=211) and normal breast tissues (n=50). In normal breast tissues, ING3 protein was detected in both the cytoplasm and nucleus. In breast cancer tissues, ING3 protein was principally detected in the cytoplasm. Compared with normal breast tissues, the expression of ING3 in nucleus was remarkably reduced in breast cancer tissues. The downregulated ING3 in nucleus was significantly correlated with clinicopathological characteristics including histological grade, lymph node metastasis, and the status of ER and PR. In HER2 positive-type and triple-negative breast cancer (TNBC) patients, it had the lower rate of nuclear ING3 with high expression than that in luminal-type. Moreover, Kaplan-Meier curves demonstrated that the reduced expression of ING3 in nucleus was correlated with a poorer 5-DFS and 5-OS of breast cancer patients. Importantly, multivariate Cox regression analysis suggested that the reduced expression of ING3 in nucleus was an independent prognostic factor in breast cancer. Our study comprehensively described the expression of ING3 in breast cancer for the first time and proved that it was an independent prognostic predictor of breast cancer, as well as a new idea for study of breast cancer.